2021
DOI: 10.3390/molecules26226825
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Activities of Halogenated Emodin Derivatives against Human Coronavirus NL63

Abstract: The current COVID-19 outbreak has highlighted the need for the development of new vaccines and drugs to combat Severe Acute Respiratory Syndrome-Coronavirus-2 (SARS-CoV-2). Recently, various drugs have been proposed as potentially effective against COVID-19, such as remdesivir, infliximab and imatinib. Natural plants have been used as an alternative source of drugs for thousands of years, and some of them are effective for the treatment of various viral diseases. Emodin (1,3,8-trihydroxy-6-methylanthracene-9,1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…In order to improve the activity of emodin against human coronavirus NL63 (HCoV-NL63) and also to generate a set of initial SAR guidelines, Monika et al prepared emodin derivatives and found that halogenation of emodin can improve the antiviral activity of which. Moreover, the most active compound was the iodinated emodin analogue E_3I, the anti-HCoV-NL63 activity of which was comparable to that of remdesivir ( Horvat et al, 2021 ). Of course, studies on emodin against COVID-19 to date are all based on in vitro experiments and there is limited discussion of its mechanisms, so more researches are needed to demonstrate the important role of emodin could play in this plague.…”
Section: Antiviral Activity Of Emodinmentioning
confidence: 92%
“…In order to improve the activity of emodin against human coronavirus NL63 (HCoV-NL63) and also to generate a set of initial SAR guidelines, Monika et al prepared emodin derivatives and found that halogenation of emodin can improve the antiviral activity of which. Moreover, the most active compound was the iodinated emodin analogue E_3I, the anti-HCoV-NL63 activity of which was comparable to that of remdesivir ( Horvat et al, 2021 ). Of course, studies on emodin against COVID-19 to date are all based on in vitro experiments and there is limited discussion of its mechanisms, so more researches are needed to demonstrate the important role of emodin could play in this plague.…”
Section: Antiviral Activity Of Emodinmentioning
confidence: 92%
“…Emodin ( 1 ) reportedly exhibits laxative, antibacterial and anti-inflammatory effects (Akkol et al 2021 ). Additionally, it might exhibit potential antiviral activity against SARS-CoV-2 (Horvat et al 2021 ), being one of the most active components of Lianhua Qingwen, a traditional antiviral Chinese medicine formulation (Runfeng et al 2020 ).
Fig.
…”
Section: Chaetomium -Derived Secondary Metabolitesmentioning
confidence: 99%
“…38,39 A very recent study by Horvat et al also demonstrated the antiviral activity of emodin derivatives against human CoVs NL63. 40 However, longstanding use of emodin may cause renal toxicity, hepatotoxicity, and reproductive toxicity. 31…”
Section: Emodinmentioning
confidence: 99%